PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PASTA GIGI PEPSODENT DI KECAMATAN BANJARMASIN BARAT - Zenni Ariantini; Erni Alfisah; Muthia Harnida (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The aim of this research is to investigate the effect of mix marketing which consists of product, price, distribution, and promotion on the purchace of Pepsodent product at the district of West Banjarmasin.This research is a survey using 100 people as respondents. The data is analyzed using multiple regression analysis. The result of this research indicated that the mix marketing of product, distribution, and promotion statistically have significant effect on purchacing the pepsodent product at the district of west Banjarmasin. But, the price in the result of this research statistically could not give the evidence of its effect on purchasing the pepsodent product for the consumers at the district West Banjarmasin . Key words: Mix marketing, price, product, promotion, purchasing